2D SQIF arrays using 20 000 YBCO high Rn Josephson junctions. (26th April 2016) - Mitchell, E E; Hannam, K E; Lazar, J; Leslie, K E; Lewis, C J; Grancea, A; Keenan, S T; Lam, S K H; Foley, C P
Abstract: Superconducting quantum interference filters (SQIFs) have been created using two dimensional arrays of YBCO step-edge Josephson junctions connected together in series and parallel configurations via superconducting loops with a range of loop areas and loop inductances. A SQIF response, as evidenced by a single large anti-peak at zero applied flux, is reported at 77 K for step-edge junction arrays with the junction number N = 1 000 up to 20 000. The SQIF sensitivity (slope of peak) increased linearly with N up to a maximum of 1530 V T −1 . Array parameters related to geometry and average junction characteristics are investigated in order to understand and improve the SQIF performance in high temperature superconducting arrays. Initial investigations also focus on the effect of the SQUID inductance factor on the SQIF sensitivity by varying both the mean critical current and the mean inductance of the loops in the array. The RF response to a 30 MHz signal is demonstrated.